New Atheism - Cañón Loyes, Camino (Pensamiento. Revista de Investigación e Información Filosófica, 2015)
Is there, at the present, strong and plausible philosophical reasons for being an atheist or, in any case, to reject religion? The New Atheism gives arguments, tipically neopositivists, to criticize religious beliefs. But its authors do it with the language of the current achievements of science. Without never take into account its intrinsic limits and showing great ignorance of the interpretation of religious beliefs of the communities that profess them. They are especially critical of what, they consider, the potential for violence of those beliefs. Its widespread not to be found in their theoretical contributions, but have generates a cultural movement in the web never imaginable by classical atheists. The critical dialogue with the new atheism requires an overhaul of the philosophical arguments in the context of science and contemporary culture, singularly the naturalism, as a question widespread in the cultural processes of naturalization of spirituality, «the really hard problem» of the neuroscience.